2012
DOI: 10.1164/rccm.201107-1190oc
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Face Masks Worn by Patients with Multidrug-Resistant Tuberculosis

Abstract: Rationale: Drug-resistant tuberculosis transmission in hospitals threatens staff and patient health. Surgical face masks used by patients with tuberculosis (TB) are believed to reduce transmission but have not been rigorously tested. Objectives: We sought to quantify the efficacy of surgical face masks when worn by patients with multidrug-resistant TB (MDR-TB). Methods: Over 3 months, 17 patients with pulmonary MDR-TB occupied an MDR-TB ward in South Africa and wore face masks on alternate days. Ward air was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 23 publications
4
138
0
11
Order By: Relevance
“…The original Riley study 466 found that the 98% reduction in infectiousness from patients with drug-susceptible tuberculosis occurred almost immediately, since treatment was started only on hospital admission, not 2 weeks before. Since then, in South Africa, Dharmadhikari and colleagues 467 found transmission only from patients with unsuspected XDR tuberculosis who were inadequately treated with MDR drugs rather than those The Lancet Respiratory Medicine Commission patients that received effective treatment. In their study, more than a hundred patients with MDR tuberculosis just started on effective therapy were exposed to hundreds of sentinel guineapigs.…”
Section: Insights Into the Effect Of Treatment On Transmission Using mentioning
confidence: 99%
See 1 more Smart Citation
“…The original Riley study 466 found that the 98% reduction in infectiousness from patients with drug-susceptible tuberculosis occurred almost immediately, since treatment was started only on hospital admission, not 2 weeks before. Since then, in South Africa, Dharmadhikari and colleagues 467 found transmission only from patients with unsuspected XDR tuberculosis who were inadequately treated with MDR drugs rather than those The Lancet Respiratory Medicine Commission patients that received effective treatment. In their study, more than a hundred patients with MDR tuberculosis just started on effective therapy were exposed to hundreds of sentinel guineapigs.…”
Section: Insights Into the Effect Of Treatment On Transmission Using mentioning
confidence: 99%
“…Surgical masks on patients were shown to be about 50% effective in preventing transmission of tuberculosis from people to guineapigs. 467 This risk reduction is equivalent to doubling the building ventilation, so is neither insignificant, nor completely effective.…”
Section: Respiratory Protectionmentioning
confidence: 99%
“…During a 4-yr period, for example, Riley estimated an average concentration of infectious quanta of 1 in 11,000 cf (311 m 3 ) and also calculated that this extremely low average concentration was sufficient to explain the rates of transmission to student nurses in hospitals during the prechemotherapy era (Riley 1957;Riley et al 1962). This same approach, using guinea pigs to quantify infectious quanta, has been used to measure the impact of such interventions as ultraviolet air disinfection, electrostatic precipitators, surgical masks on patients, and, most importantly, effective treatment as discussed below (Escombe et al 2009;Dharmadhikari et al 2012Dharmadhikari et al , 2014.…”
Section: Airborne Mycobacterium Tuberculosismentioning
confidence: 99%
“…More details on respirator use and fit testing are available on line (http:// www.cdc.gov/niosh/npptl/topics/respirators/ disp_part/) (Coffey et al 2002). Surgical masks are sometimes recommended for patients who cannot cover their coughs or sneezes, they are less expensive in one study; however, they provided only a 53% reduction in infectious cough aerosol (Dharmadhikari et al 2012). This is not insignificant, the equivalent reduction to doubling room ventilation, but it does not assure that transmission will not occur.…”
Section: Respiratory Protectionmentioning
confidence: 99%
“…2 TB infection control (IC) measures aimed at reducing the risk of TB transmission are well recognised. 3,4 Although a number of initiatives have been adopted for IC in health care settings, [5][6][7][8] limited work has been done to reduce the risk in patients' households. 9 Similar to the situation seen in health care workers in direct contact with TB patients attending health care facilities, 10 the incidence of active TB disease among household contacts of TB patients also exceeds that reported in the general population.…”
mentioning
confidence: 99%